THE PERCEIVED IMPACT OF TIKTOK AS A LEARNING MEDIUM FOR SPEAKING ENGLISH: A QUALITATIVE STUDY WITH ENGLISH EDUCATION STUDENTS (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the impact of using TikTok as an informal digital learning medium for developing English speaking skills. With its growing popularity, TikTok has become an important platform for authentic language practice, yet its use in the EFL context in Indonesia still lacks a unified theoretical framework. This study aims to (1) explore how university students use and perceive TikTok, (2) analyze its impact on their speaking proficiency and confidence, and (3) identify the challenges and self-regulation strategies they develop. This research employs a qualitative case study approach involving five English teacher training students selected through purposive sampling. The criteria include students who actively use TikTok for learning and practicing speaking, utilize its features, and demonstrate good speaking ability based on academic performance. Data were collected through in-depth interviews and analyzed thematically by integrating Social Learning Theory (SLT), Communicative Competence Theory (CCT), and Krashen’s Monitor Model. The findings reveal that students act as autonomous agents who strategically utilize the platform’s features. TikTok is perceived to have a holistic impact, improving both linguistic aspects (pronunciation and fluency) and affective factors such as self-confidence. The integration of the three theories provides a strong explanatory framework, particularly through Krashen’s Affective Filter concept, which highlights the role of confidence. The study implies that educators should shift their role toward facilitating digital literacy and metacognitive skills.